Validation of the Jamaican version of the Oral Health Impact Profile (OHIP-14) in adults: JAM-OHIP study - Brown, Michelle Antonette; Thomas, Biney; de Souza, Juliana Sena; Soares Rech, Rafaela; Santosh, Arvind Babu Rajendra; Baumgarten, Alexandre; Campbell-Blagrove, Susanna (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: The Oral Health Impact Profile (OHIP-14) is a widely used tool for measuring the effects of oral health-related quality of life (OHRQoL). However, the validity of the OHIP-14 in the Jamaican context, referred to as the Jamaican Oral Health Impact Profile (JAM-OHIP), has yet to be established. Purpose: To determine the validity of the Jamaican language version of the OHIP in evaluating the OHRQoL of Jamaican adults. Methods: The original English version of the Oral Health Impact Profile (OHIP-14) was translated into the Jamaican language using forward and backward translation. The JAM-OHIP was used to evaluate the OHRQoL of 236 individuals at the University of the West Indies Dental Polyclinic. The overall fit was checked using a chi-square test (p > 0.05), comparative fit index (CFI), Tucker–Lewis index (TLI), root mean square error of approximation (RMSEA), and standardized root mean square residual (SRMR). Results: More DMFT (p < 0.01) was associated with high JAM-OHIP scores, and the most impacted domain was physical pain. Cronbach’s alpha and the standardized item alpha for the JAM-OHIP were 0.82. The overall fitting results for the CFA were χ²(68) = 80.558, p = 0.142, and χ²/g.l. = 1.185. The CFI and TLI were 0.996 and 0.994, respectively. The SRMR was 0.072 and the RMSEA was 0.028 (CI95% = [0.000; 0.050]) p = 0.953. Conclusions: The JAM-OHIP instrument was shown to be reliable and valid for the assessment of OHRQoL in the Jamaican adult population.